Correlation Ankle Brachial Index and Inlow’s Foot Screening Among Diabetes Patient at Tourism Area in Buleleng - Udrayana, Oka; Purnamayanti, Ni Kadek Diah; Gautama, Made Satya Nugraha; Pratiwi, Luh Dea; Wirawan, Alfonsius Ade (Sekolah Tinggi Ilmu Kesehatan RS Husada, 2025)
Foot complications are a financial burden because treatment is comprehensive and lasts a long time. The prevalence of foot complications occurs repeatedly in every diabetes patient, so skills are needed to carry out early detection of diabetic foot complications. Early detection can be done with a non-invasive procedure using a simple technique, known as an ankle brachial index (ABI) examination. Other examination techniques are carried out comprehensively through inspection, palpation, and neurological examination using low's 60 second foot screening. This study aims to determine the relationship between ABI and Inlow's 60 second foot screening in type II diabetes mellitus patients in primary health facilities in Buleleng Regency. The design of this research was cross sectional carried out in September 2024. The population in this study were diabetes patients who were members of prolanis assisted by a community health center in Buleleng Regency. The total sample was 168 people. The research results showed a correlation between ABI examination results and Inlow's foot screening (p=<0.001). Routine diabetic foot examinations need to be carried out at primary health facilities for mapping, treatment and referral.